The colour stability of nanofilled composite resin after immersion in pomegranate juice: a laboratory experimental study - Widyastuti, Wiena; Gabriela, Maria; Zulkifly, Dinie Qurratuaini (Universitas Padjadjaran, 2024)
Introduction: Composite resin is highly valued for its aesthetic appeal, as its colour closely resembles that of natural teeth. Nanofilled composite resins, in particular, offer impressive colour stability. However, restorative materials can undergo colour changes due to intrinsic and extrinsic factors. One such extrinsic factor is fruit pigments, like those found in pomegranates. This study aims to analyze the colour stability of nanofilled composite resin after immersion in pomegranate juice. Methods: This laboratory experiment utilized a pre-test and post-test control group design. A total sample of forty nanofilled composite resins (Filtek Z350 XT), each with a diameter of 10 mm and a thickness of 2 mm, was divided into four groups. Each sample in the two treatment groups was immersed in 10 mL of commercial pomegranate juice for one day and seven days, respectively. Meanwhile, each sample in the two control groups was immersed in 10 mL of distilled water for the same duration. Colour measurements were carried out before and after immersion using a spectrophotometer. The data were statistically analyzed using the Shapiro-Wilk normality test to assess distribution. For normally distributed data, a one-way ANOVA was conducted, followed by the Tukey HSD post-hoc test for significant differences. For non-normally distributed data, the Kruskal-Wallis test was applied, followed by the Mann-Whitney post-hoc test if significant differences were observed. Results: The one-way ANOVA test for the L parameter yielded a p-value of 0.067 (p>0.05), indicating no significant changes after immersion in both pomegranate juice and distilled water. The Kruskal-Wallis test yielded p-values of 0.000 for E, 0.001 for C, and 0.000 for H (p<0.05), demonstrating substantial differences after immersion in both pomegranate juice and distilled water. Conclusion: The nanofilled composite resin exhibited minimal discolouration after immersion in pomegranate juice, as evidenced by changes in E, C, and H. No significant change was observed in L.